An Essay on Economic Reforms and Social Change in China - Assar Lindbeck (Research Institute of Industrial Economics (IFN), 2006)
This paper applies a systems-oriented, holistic approach to Chinas radical economic reforms during the last quarter of a century. It characterizes Chinas economic reforms in terms of a multidimensional classification of economic systems. When looking at the economic consequences of Chinas change of economic system, I deal with both the impressive growth performance and its economic costs. I also study the consequences of the economic reforms for the previous social arrangements in the country, which were tied to individual work units: agriculture communes, collective firms and state-owned enterprises. I continue with the social development during the reform period, reflecting a complex mix of social advances, mainly in terms of poverty reduction, and regress for large population groups in terms of income security and human services, such as education and, in particular, health care. Next, I discuss Chinas future policy options in the social field, whereby I draw heavily on relevant experiences in developed countries over the years. The future options are classified into three broad categories: policies influencing the level and distribution of factor income, income transfers including social insurance, and the provision of human services.
Keywords: I18; I19; I38; O53; P30; 330; China; Transition Economies; Social Insurance; Human Services; Wirtschaftsreform; Systemtransformation; Sozialer Wandel; Sozialpolitik; China